Pacritinib: A novel therapeutic agent for treating myelofibrosis - Meducator, The; Patel, Kashyap; Zheng, Ruby (The Meducator, 2019)
Selective inhibitors are an important advancement in clinical medicine, providing a method to target proteins within signal transduction pathways. One such inhibitor, pacritinib, targets Janus Kinase 2 (JAK2) to treat patients with myelofibrosis (MF). In MF patients diagnosed with a specific point mutation (JAK2V61F), the JAK/STAT pathway is over-activated, leading to an increase in cell proliferation rates. Pacritinib restores normal JAK/STAT activity by targeting aberrant activity of JAK2V61F mutant proteins and inhibiting cell proliferation in bone marrow tissue. In recent studies, pacritinib has shown better results at treating MF than the best available therapy. Though pacritinib is a potentially effective treatment option, it does not address all aspects of MF and should be supplemented with other treatments.